DEVELOPING SPEAKING SKILL OF GRADE VIII STUDENTS THROUGH PAIR WORK TECHNIQUE AT SMPN 14 PALU - Gabriela Ato; Mawardin M. Said; Wahyudin Wahyudin; Abdul Kamaruddin (e-Journal of ELTS (English Language Teaching Society), 2026)
This study aimed to determine whether the Pair Work Technique could improve the speaking skill of Grade VIII students at SMP Negeri 14 Palu. A quasi-experimental design was employed involving two classes: Class VIII Albert Einstein as the experimental group (n = 31) and Class VIII Habibie as the control group (n = 27). Both groups were given a pre-test and a post-test to measure students’ speaking achievement. The instrument used was an oral speaking test assessed through a fluency-based scoring rubric. The treatment was conducted over six meetings in the experimental group using structured pair work activities, while the control group received conventional instruction. The pre-test results showed that students in both groups had low speaking ability before the treatment. After the implementation of the Pair Work Technique, the experimental group demonstrated greater improvement than the control group. The post-test results showed that 27 of 31 students in the experimental group met the passing criterion, compared to 17 of 27 students in the control group. The independent samples t-test showed that the obtained t-value (2.79) was higher than the critical t-value (2.009) at the 0.05 significance level with 56 degrees of freedom. The findings indicate that the Pair Work Technique significantly improved students’ speaking skill. Therefore, Pair Work Technique can be considered an effective strategy for developing students’ speaking fluency through increased practice, interaction, and participation in the classroom.